Salticidae (Arachnida: Araneae) of New Caledonia: Genus Corambis Simon, 1901 - Patoleta, Barbara; Żabka, Marek (European Journal of Taxonomy, 2019)
The genus Corambis Simon, 1901 includes five species; three of them, C. jacknicholsoni sp. nov., C. logunovi sp. nov. and C. pantherae sp. nov., are described here as new. The female of the C. foeldvarii Szűts, 2002 is described for the first time and a new generic diagnosis is proposed. The distribution and relationships of Corambis are discussed in terms of the geological and bioclimatic history of New Caledonia.